Lives as Collections of Strands: An Essay in Descriptive Psychology. (March 2020) - Kubovy, Michael
In this article I generalize the notion of multiple self-aspects to create a descriptive framework in which lives are partitioned into containers of activities called strands. Strands are nearly decomposable life modules, structured, stable, and concurrent longitudinal streams of extended duration whose momentary cross-sections constitute self-aspects. They are differentiated by five features: the person's role, the cast, the setting, norms and values, and habits and routines. Strands contain projects and episodes and are replete with narrative. Each strand is continuous (i.e., strands persist when a person moves between them), and for the most part strands are mutually asynchronous. From a first-person perspective, the strands are continuous and concurrent, but only one strand is in the foreground at a given time (i.e., transitions between strands are akin to a figure-ground reversal). Furthermore, a life is different from the sum of its strands: It is a nonlinear system that can take on configurations not predictable from a comprehensive description of the individual strands. Two such examples are the achievement of greatness despite severe handicaps and instances of extreme self-sacrifice. I also discuss the research potential of a proposed smartphone app called LifeMaps.